PENINGKATAN KOMITMEN ORGANISASIONAL MELALUI KEADILAN ORGANISASI DAN KEPUASAN KERJA (STUDI PADA PT INTI GRAFIKA PAPERINDO DENPASAR) - Putu Prasitaning Ayu Saraswati; Ni Luh Adisti Abiyoga Wulandari; I Gede Aryana Mahayasa (Warmadewa Management and Business Journal (WMBJ), 2023)
Human resources who are loyal, satisfied, consistent with organizational goals and values tend to maintain an organization's membership beyond the specified tasks can be an important factor in organizational effectiveness. This study aims to understand the effect of organizational justice and job satisfaction on the organizational commitment of PT Inti Grafika Paperindo in Denpasar. The research method used is quantitative. The research location is at PT Inti Grafika Paperindo in Denpasar. The sample used was 39 respondents. The data analysis techniques used are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t Test and F Test. Based on the results of the study, it was found that organizational justice has a significant positive effect on organizational commitment, job satisfaction has a significant positive effect on organizational commitment, and simultaneously organizational fairness and job satisfaction have a positive and significant effect on organizational commitment. The magnitude of the independent variable's influence on organizational commitment was 74.2%. The advice in this study is that PT Inti Grafika Paperindo should always be fair to employees and increase employee job satisfaction and make salary policies that are in accordance with the tasks carried out by employees.